J-band amplifier design using gain-enhanced cascodes in 0.13 μm SiGe. Issue 3 (26th May 2015) - Malz, Stefan; Heinemann, Bernd; Lachner, Rudolf; Pfeiffer, Ullrich R.
Abstract : This paper presents two J-band amplifiers in different 0.13 μm SiGe technologies: a small signal amplifier (SSA) in a technology in which never before gain has been shown over 200 GHz; and a low noise amplifier (LNA) design for 230 GHz applications in an advanced SiGe HBT technology with higher fT/fmax, demonstrating the combination of high gain, low noise, and low power in a single amplifier. Both circuits consist of a four-stage pseudo-differential cascode topology. By employing series–series feedback at the single-stage level the small-signal gain is increased, enabling circuit operation at high-frequencies and with improved efficiency, while maintaining unconditional stability. The SSA was fabricated in a SiGe BiCMOS technology by Infineon with fT/fmax values of 250/360 GHz. It has measured 19.5 dB gain at 212 GHz with a 3 dB bandwidth of 21 GHz. It draws 65 mA from a 3.3 V supply. On the other hand, a LNA was designed in a SiGe BiCMOS technology by IHP with fT /fmax of 300/450 GHz. The LNA has measured 22.5 dB gain at 233 GHz with a 3 dB bandwidth of 10 GHz and a simulated noise figure of 12.5 dB. The LNA draws only 17 mA from a 4 V supply. The design methodology, which led to these record results, is described in detail with the LNA as an example.